ISLAM AND World History : The Ventures of Marshall Hodgson - Burke, Edmund; Mankin, Robert (Silk roads, 2018)
Marshall Hodgson’s The Venture of Islam was a watershed moment in the study of Islam. By locating the history of Islamic societies in a global perspective, Hodgson challenged the orientalist paradigms that had stunted the development of Islamic studies and provided an alternative approach to world history. Edited by Edmund Burke III and Robert Mankin, Islam and World History explores the complexity of Hodgson’s thought, the daring of his ideas, and the global context of his world historical insights into, among other themes, Islam and world history, gender in Islam, and the problem of Muslim universality.